Gyroscopic System Based on Wave Solid-State Gyros - Malyutin, D.M.; Korolyev, M.N. (2020 27th Saint Petersburg International Conference on Integrated Navigation Systems (ICINS), 2020)
A mathematical description for the stabilization loop of a gyroscopic stabilizer is given. The sensitive element of the loop is a wave solid-state gyroscope operating in the mode of an angular velocity sensor. Simulation and study of the dynamic characteristics of a gyroscopic stabilizer on a solid-state gyroscope are performed.